Efektivitas Peraturan Daerah Kabupaten Bangli Nomor 15 Tahun 2011 tentang Pajak Hotel - I Wayan Geng Krisna; Ida Ayu Putu Widiati; Luh Putu Suryani (Warmadewa Press, 2020)
Over time with the development of the economy in Bangli Regency, especially in the field of tourism, developments in the field of tourism will lead to an increase in the number of tourists coming to Bangli both local and foreign tourists. So it has a positive relationship with the increasing number of hotels in Bangli, as well as causing the growth of hotels in Bangli to develop rapidly. This shows that hotel tax has an important role in encouraging regional development and increasing local revenue in Bangli Regency. Referring to the matter of this writing problem as follows: how is the effectiveness of the Regional Regulation of Bangli District Number 15 of 2011 concerning Hotel Taxes on the increase of Local Original Revenue (PAD) in the Regency of Bangli and how to increase the Regional Original Income carried out by the Bangli Regency government in implementing Regional Regulation Number 15 of 2011 concerning Hotel Taxes. This research uses empirical legal research. The results showed that: The effectiveness of Bangli Regency Regulation Number 15 of 2011 concerning Hotel Taxes based on the realization of Bangli Regency revenue targets has been effective. This result can be seen from the achievement of the tax realization target in Bangli Regency in the last 3 (three) years, namely: 2017 with a target of 50,000.0000.00 realization of 84,101,819.00 with a percentage of 168.20%. 2018 with a target of 65,000,000.00 realization of 73,130,121.00 with a percentage of 112.51%. 2019 with a target of 80,000,000.00 realization of 142,655,151.40 with a percentage of 178.32%. Efforts to increase hotel tax collection carried out by the Bangli Regency Regional Revenue and Asset Financial Agency are the first to conduct direct socialization to the community, the second to provide reawed or rewards to taxpayers who have obeyed their obligation to pay taxes, the third routinely verify taxpayer data, in addition to The effort made by the Bangli Regency Government in increasing hotel tax collection is by making effective tax collection using forced letters so that hotel tax collection in Bangli Regency is increasing and giving sanctions to taxpayers if they do not have the obligation to pay taxes.